The Capicua repressor – a general sensor of RTK signaling in development and disease - Jiménez, Gerardo (Company of Biologists, 2012)
Receptor tyrosine kinase (RTK) signaling pathways control multiple cellular decisions in metazoans, often by regulating the expression of downstream genes. In Drosophila melanogaster and other systems, E-twenty-six (ETS) transcription factors are considered to be the predominant nuclear effectors of RTK pathways. Here, we highlight recent progress in identifying the HMG-box protein Capicua (CIC) as a key sensor of RTK signaling in both Drosophila and mammals. Several studies have shown that CIC functions as a repressor of RTK-responsive genes, keeping them silent in the absence of signaling. Following the activation of RTK signaling, CIC repression is relieved, and this allows the expression of the targeted gene in response to local or ubiquitous activators. This regulatory switch is essential for several RTK responses in Drosophila, from the determination of cell fate to cell proliferation. Furthermore, increasing evidence supports the notion that this mechanism is conserved in mammals, where CIC has been implicated in cancer and neurodegeneration. In addition to summarizing our current knowledge on CIC, we also discuss the implications of these findings for our understanding of RTK signaling specificity in different biological processes.